Characterization and control of energetic deposits from hexachlorodisilane in process tool exhaust lines. (May 2020) - Nguyen, Thanh-Trung; Lin, Yu-Jhen; Chin, Mo-Geng; Wang, Cheng-Chieh; Tsai, Hsiao-Yun; Chen, Jenq-Renn; Ngai, Eugene Y.; Chacon, Jennyfer; Franzi, Albert; Fifield, Christian; Baylor, Jason; Marci, John; et al.
Abstract: This work aims to characterize and develop a disposal method for a gel-like deposit generated in a vacuum foreline of an atomic layer deposition (ALD) tool that is using hexachlorodisilane (Si2 Cl6, HCDS) as a precursor. This ALD foreline gel was reproduced by replicating the ALD tool process conditions by using a benchtop system that was a 1/85 scale down of one user's process. All samples were tested for shock sensitivity using the Fall hammer apparatus. Extensive infrared studies were done for unhydrolyzed and hydrolyzed gel. Dissolution tests were conducted to develop a method for removing and disposing the gel off-site. Many different solutions such as solvent based solutions, water based alkaline solutions and alcohol based alkaline solutions were tested. It was found that alcohol based alkaline solutions produced only hydrogen as a byproduct and were considered satisfactory for off-site abatement of gel. Furthermore, in-situ cleaning gel of the foreline using a fluorine/N2 mixture with a concentration of 1–10vol% was done. They were all effective in cleaning/removing the gel under the condition of ambient temperature and reduced pressure. Finally, recommended procedures were given for removing as well as disposing the ALD gel. Highlights: To reproduce the gel-like substance from Hexachlorodisilane in process tool exhaust lines. To characterize fire and explosion hazards of this gel and its hydrolysis product. To propose the safe disposal methods for this gel and its hydrolysis product.